2022
DOI: 10.3390/f13020292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Juvenile, Drought Tolerant Black Locust (Robinia pseudoacacia L.) Clones with Regard to Plant Physiology and Growth Characteristics in Eastern Hungary: Early Evaluation

Abstract: (1) Background: The aim of our study is to present the results of initial growth and plant physiology studies of newly selected, vegetative propagated black locust clones, with a view to assess their suitability for the establishment of fast growing tree plantations for the production of high quality timber in marginal (semi-arid) sites. (2) Methods: In the spring (May) and autumn (November) of 2021, full inventories were carried out in the black locust industrial tree plantation. The Normalized Difference Veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…This research effort resulted in several state-approved cultivars [5,28,30,31]. Suitability for the establishment of black locust plantations in marginal sites with extreme weather conditions, especially drought, can be expected to differ by clones, as proved by our preliminary investigation [32]. It must be noted that utilization determines which parameter has priority.…”
Section: Introductionmentioning
confidence: 97%
“…This research effort resulted in several state-approved cultivars [5,28,30,31]. Suitability for the establishment of black locust plantations in marginal sites with extreme weather conditions, especially drought, can be expected to differ by clones, as proved by our preliminary investigation [32]. It must be noted that utilization determines which parameter has priority.…”
Section: Introductionmentioning
confidence: 97%
“…He et al [ 30 ] found that this species has physiological responses of strong stomatal control to drought in the sub-humid region of the Loess Plateau. However, some clones of black locust can tolerate water stress and were considered as drought-tolerant type in Napkor [ 34 ]. The black locust showed relatively lower sensitivity of stomatal conductance to environmental factors in a semiarid site [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…recently established an experimental plantation that included a clone trial involving four newly-bred clones and a state-approved cultivar -Üllői black locust (Rédei et al 2020) as a control. The trial compared these new clones and the Üllői cultivar for growth, assimilation parameters and water use efficiency (Ábri et al 2022, 2023bÁbri, Csajbók 2023).Many stress factors negatively affect plants today. Global climate change has increased the two…”
mentioning
confidence: 99%
“…Many studies have examined black locust physiology and water stress response (Zheng et al 2012;Mantovani et al 2014;Meng et al 2014;Küppers et al 2018;Choi et al 2021;Lange et al 2022;Ábri et al 2023b;Ábri, Csajbók 2023). Zheng et al (2012) demonstrated that black locust photosynthetic light response curves initially show a rapid increase in the net CO 2 assimilation rate (A) under photosynthetically active radiation (PAR) between 0 μmol•m -2 •s -1 and 200 μmol•m -2 •s -1 .…”
mentioning
confidence: 99%